AB0614 Antisynthetase syndrome: autoantibodies, clinical pattern and management of 17 spanish patients. (15th June 2017) - Busca, C; Robles, Ά; Vives, I; Troncoso, JA; Bailόn, L; Ríos, JJ; Noblejas, A; Arnalich, F
Abstract : Background: Antisynthethase syndrome (ASS) is a heterogeneous rare inflammatory condition characterized by myopathy, intersticial lung disease (ILD), arthritis, mechanic hands and Raynaud phenomenon (RP). The hallmark of ASS is the presence of antibodies against aminoacyl-transfer RNA synthetases (anti-ARS). Eight different anti-ARS have been described: anti-Jo1, anti-PL7, anti-PL12, anti-EJ, anti-OJ, anti-KS, anti-Zo, anti-Tyr/YRS. Despite recent publications, correlation between autoantibodies clinical pattern and management in ASS is not entirely well-known. Objectives: The aim of this study was to define clinical features, autoantibodies and outcomes of a series of ASS patients. Methods: We retrospectively analyzed the epidemiology, clinical data, lung function parameters, muscle enzymes, electromyogram (EMG) and autoantibodies pattern and its relationship with clinical manifestations, treatment management and outcomes of 17 patients recruited between 2005 and 2016 from the Autoimmune Diseases Division of a Spanish hospital. Results: A total of 17 patients were reviewed (15 female). Mean age at diagnosis was 55 years. Median time delay to diagnosis was 5 months. Median follow-up was 65 months. Main clinical symptoms were dyspnea (76.5%), polyartrhitis (58.6%), muscle weakness and myalgias (52.9%), RP (41.1%) and mechanic hands (23.5%). Lung involvement was defined by HRCT compatible with ILD (64.7%) and abnormal functional exploration (47.1%): restrictive pattern (87.5%) and diminished DLCO (61%). Muscle involvement was defined by elevated CK (52.9%) with a median maximum value of 517 IU/L, myopathic pattern on 8 of 13 performed EMG (61.1%) with myositis found in 4 of them (50%), and inflammatory myositis in 5 of 8 performed biopsies (62.5%). Anti-ARS findings were anti-Jo1 (11), PL12 (2), PL7 (1), anti-EJ (2) and one patient with both PL7 and PL12. Anti-Jo1 predominant clinical pattern was ILD (72.7%), followed by myopathy (63.6%) and concomitant myopathy and ILD (45.5%). Anti-PL12 was associated with ILD, RP, and esophageal involvement and no myopathy. Anti-PL7 patient showed mild myopathy and cutaneous association alone. A combination of anti-PL12 and PL7 was described in one patient who developed ILD with severe myopathy. Anti-EJ patients had pulmonary involvement but no evidence of muscle disease. There was no evidence of cancer in any of our patients. Corticosteroids therapy was administered in most of them (88.2%), and corticodependence was highlighted, being necessary at times to associate one or more immunosuppressants. Conclusions: Regardless of ASS being a rare disease, 17 patients were collected. Anti-Jo1 was the most described antibody. It is important to note that one patient was found to be positive for both anti-PL7 and PL12 meanwhile they were described as exclusive, showing overlap of clinical pattern with severe muscle injury. This finding suggests that positive results for more than one ASS antibody infer more severity. In contrast with previous literature, pulmonary was more frequent than muscle involvement. The coexistence of both was observed in a small group (35.3%), mostly in anti-Jo1 patients (45.5%). Therefore, we suggest the need to request ASS antibodies in patients with pulmonary or/and muscle involvement at onset although classic clinical pattern is missing. References: Mirrakhimov AE. Curr Med Chem. 2015;22 (16):1963–75. Disclosure of Interest: None declared